The realisation of the righ access to health care services for refugees and Asylum seekers inSouth Africa - Kozah, Melody Rumbidzai (Centre for Law and Society, 2026)
Human rights are universal, inalienable and inalterable therefore all persons should, by virtue of their essential humanity, enjoy all human rights.1 The right to health is a fundamental part of our human rights. It contains freedoms such as the right to be free from non consensual medical treatment and entitlements.2 The entitlements include the right to a system of health protection providing equal opportunity for everyone to enjoy the highest attainable level of health.3 This dissertation focuses on the latter with regard to refugees and asylum seekers in South Africa whose health care needs are not met. The Office of the United Nations High Commissioner has emphasised that, 'exceptional distinctions, between citizens and non-citizens in the enjoyment of human rights can be made only if they serve a legitimate State objective and are proportional to the achievement of that objective'. In South Africa refugees and asylum seekers are unable to assert their right of access to health care effectively. They experience xenophobia, language barriers, discrimination and they face difficulties in accessing information on available health care services.5 The dissertation highlights that in practice there is a large gap between the rights that South African law read with international human rights law guarantees refugees and asylum seekers and the realities that they face.6 The gap shows that South Africa is not fulfilling its obligations as set out by the law. South Africa has a duty to address this problem because according to the law it is bound to respect, protect and fulfil the right of access to health care of refugees and asylum seekers.